The cross-regulation between h1 and h2 histamine receptors modulates the behavior of h2 receptor blockers - Díaz Nebreda, Antonela (2018)
Histamine modulates severalbiological processes, including allergy and gastric acid secretion, through H1and H2 receptors (H1R, H2R). H2R blockers are mainlyused to treat gastrointestinaldisorders, such as gastric acid secretion and there is much interest on theirrepositioning for other pathologies. Thus, deepunderstanding of theirmechanisms of action is needed. We have previously described that H1R and H2Ragonists induce the receptor?s co-internalization andcross-desensitization. We havealso reported that H2R blockers lead to desensitization and internalization ofH2 receptor.The aim of this work was tostudy the capacity of H2R blockers (cimetidine, ranitidine and famotidine) toinduce the H1R cross-desensitization and how thismechanism affects the behaviorof H2R blockers. In this way, we used promonocytic U937 cells (endogenouslyexpressing H1R and H2R), PMA-differentiated U937cells and HEK293 cellstransiently transfected with one or both receptors.